Poly(4‐Vinylpyridine)‐Based Cubosomes: Synthesis, Assembly, and Loading Capabilities - Marcel Schumacher; Nadine Tänzer; Marius G. Braun; Manuel Trömer; Giada Quintieri; Mahima Goel; Markus Heidelmann; André H. Gröschel (Small Science)
Polymer cubosomes (PCs) are 3D porous microparticles with high surface area that have great potential for applications that require a large interfacial area including catalysis, drug delivery, and energy storage. Most reported PCs are based on chemically inert block copolymers (BCPs) with limited intrinsic functionality, which is why they have been mainly used as templating material. Herein, the synthesis, self‐assembly, and loading of poly(4‐vinylpyridine) (P4VP)‐based PCs are reported. The pyridinic moieties are located inside the PC wall and are well‐known functional groups for coordination, cross‐linking, and pH response, which is demonstrated on platinum coordination and pH‐dependent dye release.